High and low flowrate sampling of airborne influenza in hospital rooms during three outbreaks. (November 2021) - Dubuis, Marie-Eve; Degois, Jodelle; Veillette, Marc; Turgeon, Nathalie; Paquet-Bolduc, Bianka; Boivin, Guy; Duchaine, Caroline
Abstract: Each year, healthcare settings are confronted by outbreaks caused by influenza and infected patients produce aerosols making this route a potential issue during outbreaks. This study was conducted in an Eastern Canadian hospital during three confirmed influenza outbreaks. Air was sampled in the rooms of infected patients using a liquid cyclone sampler and an electret dry filter sampler, two high flowrate aerosol samplers. During the third outbreak, a water-based condensation sampler, which has a low flowrate, was also used for aerosol sampling. Influenza RNA concentrations were observed at up to 1.05 × 10 5 (electret dry filter sampler), 1.99 × 10 5 (liquid cyclone sampler) and 3.02 × 10 5 (water-based condensation sampler) genomes/m 3, but varied greatly between outbreaks. During the first outbreak, 14 positive samples were recovered with RNA concentrations between 6.66 × 10 2 and 1.99 × 10 5 genomes/m 3 . For the second outbreak, 18 samples were positive, but lower concentrations were detected, from 1.53 × 10 1 to 5.97 × 10 2 genomes/m 3 . Three positive samples with concentrations between 6.09 × 10 4 and 3.02 × 10 5 genomes/m 3 were recovered during the third outbreak. This study provides crucial information regarding the differences in airborne influenza viruses during three different outbreaks that took place in the same hospital. Comparisons of airborne virus concentrations in other hospital or long-term care settings would contribute to a better understanding of the role that air can play in influenza outbreaks. Highlights: Influenza bioaerosol concentrations were compared between three outbreaks. Airborne influenza RNA concentrations were up to 3.02 × 10 5 genomes/m 3 . High and low flowrate aerosol samplers were effective for influenza RNA recovery.